ONLINE AND OFFLINE METHODS OF TEACHING ENGLISH IN PHILOLOGY, ADVANTAGE AND DISADVANTAGE ASPECTS - To’lqinova Diyora Jurabekovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, the use of innovative methods of online and offline educational programs in English philology, as well as the positive and negative sides of these programs are highlighted. Every person who receives education through the three articles will have the necessary information, knowledge and skills.